The Attentional System in The Case of Harvey Weinstein Sexual Abuse Allegations on International Online News - Suherman, Rudi (CV. Ridwan Publisher, 2021)
The study aims to find out the attention system, especially, the focus of attention patterns, on news articles related to the Harvey Weinstein sexual harassment allegations case. Qualitative descriptive methods were used in this study. The data was taken from the BBC and the stylist's broadcasting article about the case. The results show that the figure-ground organization as an element in the focus of attention patterns is mapped and clearly constructed. Weinstein, who fits the role of the perpetrator, reasoned on the victim and the attention of the news writer's article that formed the ground, while the victim and other entities set the ground in the sentence. This reasoned and background phenomenon shows that the cognition of victims and news writers places more attention and perception on perpetrators than other entities.